Firm Performance and Dividends in State-owned Companies from CEE Countries – Are Polish SOEs Different? - Elżbieta Bukalska; Anita Peša (Comparative Economic Research)
In recent years, the focus on state-owned enterprises (SOE) has returned. SOEs are an important part of the post-socialist countries that comprise Central and Eastern Europe (CEE). However, there are still no consistent findings on SOEs’ performance and dividend payouts, although the popular perception is that they have lower firm performance and pay higher dividends. The paper aims to ascertain the level of firm performance of dividend payments made by these enterprises. The research includes 132 companies from 12 CEE stock markets, with 743 firm-year observations for the 2017–2022 period. For a robustness check, several measures of state ownership and dividend payouts are implemented. The main research method is a General Linear Model with country- and year-fixed effects. The research demonstrates that state ownership has a negative impact on firm performance in CEE countries but a positive on dividend payouts. However, for the Polish subsample, state ownership has had a positive impact on profitability and no impact on dividend payouts.